THE EFFECT OF WEAVING ACTIVITIES WITH BANANA LEAVES ON FINE MOTOR ABILITY EARLY OF CHILDHOOD - Irmawati Irmawati; Ichsan Ichsan (CAKRAWALA DINI: JURNAL PENDIDIKAN ANAK USIA DINI, 2021)
This research aims to determine the effect of weaving activities on fine motor skills in TK Pertiwi 26-13 Bogares Kidul. This research uses a quantitative approach method by carrying out Field Research. This research presents data in the form of numbers using statistical data analysis which has the aim of testing hypotheses and data analysis using regression analysis. The results of the research show that the regression analysis of Y = 5.592 + 0.579X, the equation shows a lot of at least a child's fine motor capacity. Banana leaf weaving affects the fine motor skills of Pertiwi Kindergarten 26-13 Bogares Kidul. The conclusions drawn are: banana leaf weaving give positive affects on fine motor skills development of Pertiwi Kindergarten 26-13 Bogares Kidul children. The contribution of the effectiveness of banana leaf weaving to fine motor skills is seventy-four percent. Based on the reaction analysis and analysis that has been carried out in this research, it can be concluded that the banana leaf weaving variable has a positive and increasing effect on fine motor skills.